2014
DOI: 10.1002/eji.201344203
|View full text |Cite
|
Sign up to set email alerts
|

B‐cell‐intrinsic STAT6 signaling controls germinal center formation

Abstract: Infection with helminths and exposure to antigens induce a strong type 2 immune response resulting in the secretion of the cytokines IL-4 and IL-13 by CD4 + T cells and several innate cell types. IL-4 and IL-13 promote class switch recombination to IgG1 and IgE while their role for germinal center (GC) formation is poorly understood. We found a dramatic reduction in the numbers of GC B cells when investigating different type 2 immune responses in IL-4/IL-13-deficient mice. IL-4/IL-13 from T cells locatedAdditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
77
2
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(85 citation statements)
references
References 32 publications
4
77
2
2
Order By: Relevance
“…Multiple genes that promote B cell germinal centre entry and persistence were upregulated in mature naïve B cells lacking GILZ, including Bak1 and Bax 53 54, Mcl-1 ,55 56 Id3 ,57 c-Myc ,54 Tlr9 ,58 Stat6 ,59 Socs3 34 and MyD88 60. Thus, naïve B cells lacking GILZ bear a transcriptional profile that may predispose towards activation, survival and germinal centre entry.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple genes that promote B cell germinal centre entry and persistence were upregulated in mature naïve B cells lacking GILZ, including Bak1 and Bax 53 54, Mcl-1 ,55 56 Id3 ,57 c-Myc ,54 Tlr9 ,58 Stat6 ,59 Socs3 34 and MyD88 60. Thus, naïve B cells lacking GILZ bear a transcriptional profile that may predispose towards activation, survival and germinal centre entry.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to antibody production, B cells have been proposed to contribute to T H 2 polarization by expression of co-stimulatory molecules such as OX40L and B7 after infection with N. brasiliensis and H. polygyrus (31, 32). In return, T-cell derived IL-4 and IL-13 signal through STAT6 on B cells, promoting the generation of germinal center responses(33). This pathway and its clinical importance are compressively described in several review articles (29, 34, 35).…”
Section: Adaptive Immunitymentioning
confidence: 99%
“…Furthermore, STAT6 is a critical regulator in IL-4-mediated B-cell differentiation. Previous work has shown that B cells from mice lacking STAT6 failed to produce significant amounts of IgE and IgG1 after infection with the nematode parasites (Raia et al, 2011;Turqueti-Neves et al, 2014). The binding sites of STAT6 have been found in the target regions of a variety of IL-4-mediated genes, including CD23 (Cooper et al, 2012), IL-4R (Jenkins et al, 2013), eotaxin-1 (Waddell et al, 2013), eotaxin-3 (Nakayama et al, 2010), FIZZ1 (Dasgupta et al, 2011), and in Ig germline e (Lu et al, 2007) promoters.…”
Section: Introductionmentioning
confidence: 99%